From Shi`a to White: Race and Colonialism in Kamel Murouwwa’s Nahnu fi Ifriqiya - Dahlia El Zein (Mashriq & Mahjar)
In 1938, Lebanese Syrian publisher Kamel Murouwwa extensively toured West Africa and produced a 329-page travelogue entitled Nahnu Fi Ifriqiya: al-Hijra al-Lubnaniyya al-Suriyya ila Ifriqiya al-Gharbiyya, Madiha, Hadirha, Mustaqbaliha (We are in Africa: Lebanese Syrian Migration to West Africa, its Past, Present, and Future). In this article, I use Murouwwa’s travelogue as a lens to understand the process of racial identity formation in West Africa from a Lebanese visitor’s perspective in the 1930s under French colonialism. Murouwwa's source has been underutilized as a rich text of thick racial description. This article argues that through the process of racial identity formation in West Africa, Lebanese Shi’is were able to transcend emerging sectarian identities prevalent in newly carved Lebanon which marked Shi’is as “metwali” (backward). Lebanese migrants’ “whiteness” became the most pronounced marker of their presence amongst local Africans, overshadowing religious identity and erasing any “backwardness” associated with Shi’is in Lebanon, elevating the community to the class of colonizer vs. colonized. Sectarianism carries significant weight within the confines of the nation-state but a broadened transnational approach to sectarianism provides a widened view to see how racial identity supplanted sectarian identity outside the nation-state.